Pengembangan Pemeriksaan Fisik Berdasarkan Kebutuhan Dasar Fisiologi Manusia Pada Usia Dewasa di RSUD Dr Slamet Garut - Dian Roslan Hidayat; Imas Pupah (STIKes Karsa Husada Garut, 2015)
Implementation of nursing care can be found with many obstacles, this is in accordance with the existing data in this study nurses have different perceptions on the implementation and the cause of the incompleteness of the nursing care documents. The purpose of this study was to develop a Physical Examination of human physiology based on age adults in hospitals dr.Slamet Garut 2014. The method used deskriptif. Variables namely Development of Physical Examination of Human Physiology Basic Needs Based On Age Adults in dr Slamet Garut 2014. The sample in this study were nurses dr Slamet Garut in adult rooms numbered 97 people. The results showed that the majority (85%) physical examination format is based on the basic needs of human physiology including the appropriate category, a small portion (15%) including category is not appropriate. Suggested to the hospital to improve nursing documentation more effective, for example by filling the nursing documentation immediately after taking action.